Das Verbot der Marktmanipulation am Beispiel von aktivistischen Leerverkäufern Eine rechtsökonomische Untersuchung der kapitalmarktrechtlichen Zusammenhänge eines neuen Phänomens - Vollmerhausen, Marcel (Mannheimer Schriften zum Unternehmensrecht, 2022)
Wirecard, Adler & Co.: The emergence of short selling attacks has led to a lively discussion about their legal permissibility under the Market Abuse Regime. The thesis addresses the exciting question under which conditions the phenomenon of activist short sellers is to be classified as prohibited market manipulation according to Art. 12 MAR. For this purpose, the business model of activist short sellers is first analysed in actual terms and then assessed against the standard of Art. 12 MAR. The focus is on the systematic coverage of the prohibition provision. The legal analysis is supported by a well-founded economic analysis.